If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1(6x + -10) = 0 Reorder the terms: 4 + -1(-10 + 6x) = 0 4 + (-10 * -1 + 6x * -1) = 0 4 + (10 + -6x) = 0 Combine like terms: 4 + 10 = 14 14 + -6x = 0 Solving 14 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -6x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -6x = 0 + -14 -6x = 0 + -14 Combine like terms: 0 + -14 = -14 -6x = -14 Divide each side by '-6'. x = 2.333333333 Simplifying x = 2.333333333
| -13=2x+3 | | -3(p+8)=-42 | | 1-3n=-2n+9 | | -564.3x^3+477.1224x^2-141.22831x+13.99345=0 | | 20y=2480 | | -39=3(v-3) | | -7x-5x= | | 2ax+5b=6cx+d | | 10+2n+1= | | 10-25x= | | 8y=0.5y^2 | | -54+2x=-4x+30 | | 5x-30=7x+16 | | 5x-30=7x+161 | | 8x-62=28+3x | | y=9(-0.7)+6 | | -73-10x=83+2x | | 12x+y=100 | | -118+4x=12x+122 | | g(-0.7)=9x+6 | | x+y=720 | | 25b+11=-16b^2 | | 5x-140=64-12x | | -66-x=150+8x | | .2r+.75=.5r | | -5x+21=11 | | -4x-91=6x+99 | | 4x+11+3x-6=180 | | -27+3x=61-x | | X-73=89-5x | | (5x+2)(5x-2)=32 | | w=20l |